Multimodality Imaging of Silica and Silicon Materials In Vivo - Karaman, Didem Şen; Sarparanta, Mirkka P.; Rosenholm, Jessica M.; Airaksinen, Anu J. (Advanced materials (Weinheim), 2018)
Recent progress in the development of silica‐ and silicon‐based multimodality imaging nanoprobes has advanced their use in image‐guided drug delivery, and the development of novel systems for nanotheranostic and diagnostic applications. As biocompatible and flexibly tunable materials, silica and silicon provide excellent platforms with high clinical potential in nanotheranostic and diagnostic probes with well‐defined morphology and surface chemistry, yielding multifunctional properties. In vivo imaging is of great value in the exploration of methods for improving site‐specific nanotherapeutic delivery by silica‐ and silicon‐based drug‐delivery systems. Multimodality approaches are essential for understanding the biological interactions of nanotherapeutics in the physiological environment in vivo. The aim here is to describe recent advances in the development of in vivo imaging tools based on nanostructured silica and silicon, and their applications in single and multimodality imaging. Silica and silicon are excellent material platforms for generating multimodality imaging probes for diagnostic and nanotheranostic applications. Being versatile materials with multifunctional properties, they can be extensively used for the creation of novel drug‐delivery systems for site‐specific nanotherapeutics. When developed into multimodality imaging probes, they are excellent tools for investigating biological interactions of the nanotherapeutics in the physiological environment.